Os programas de pesquisa em Lakatos e a análise de elementos da biologia - Silva, Lazandir João da (2024)
In this dissertation we present an analysis of Imre Lakatos' research programs, focusing on some of his main concepts, such as firm core, protective belt, surplus theoretical content, surplus empirical content, corroborated empirical content, empirical progressivity, theoretical progressivity, progressive program and degenerative, in addition to exploring concepts such as internal and external history. The study is dedicated to understanding how research programs, as defined by Lakatos, seek to help explain the development and evolution of scientific knowledge. The firm core is examined as the theoretical backbone of a program, resistant to tampering and external challenges, while the protective belt serves to adjust and protect the firm core without compromising the essential foundations. We will address the concept of surplus empirical content, which highlights observations or phenomena predicted by theory, and the way in which this content can corroborate or refute a research program. Empirical and theoretical progressivity is analyzed to understand how programs constantly seek to advance their explanations and predictions. Furthermore, we address the distinction between progressive and degenerative programs, highlighting how some programs thrive by incorporating new knowledge, while others stagnate or even decline. We also propose an analysis of the theoretical contributions of Karl Popper and Thomas Kuhn to the philosophy of science. The objective is to understand how theoretical structures have evolved over time, examining the prominence of the Darwinian program in its early stages and its competition with rivals, as well as the emergence and consolidation of the Synthetic Theory of Evolution. Next, the research explores the most recent developments with the advent of the Extended Synthesis Theory of Evolution research program, evaluating how this new program challenges and competes with the assumptions established by the Synthetic Theory. By adopting a Lakatosian approach, the dissertation aims not only to understand the history and evolution of these programs, but also to provide an analysis of current dynamics, considering the pluralism of processes and the complexity that characterizes research in evolutionary biology.